Single-Atom Fe-Anchored Nano-Diamond With Enhanced Dual-Enzyme Mimicking Performance for H2O2 and Glutathione Detection - Liu, Ying; Yan, Jianghong; Huang, Yu; Sun, Zhiheng; Zhang, Huijing; Fu, Lihaoyuan; Li, Xuwen; Jin, Yongri (Frontiers in Bioengineering and Biotechnology, 2022)
Glutathione (GSH) is an important antioxidant and free radical scavenger that converts harmful toxins into harmless substances and excretes them out of the body. In the present study, we successfully prepared single-atom iron oxide-nanoparticle (Fe-NP)-modified nanodiamonds (NDs) named Fe-NDs via a one-pot insitu reduction method. This nanozyme functionally mimics two major enzymes, namely, peroxidase and oxidase. Accordingly, a colorimetric sensing platform was designed to detect hydrogen peroxide (H2O2) and GSH. Owing to their peroxidase-like activity, Fe-NDs can oxidize colorless 3,3´,5,5´-tetramethylbenzidine (TMB) into blue with sufficient linearity at H2O2 concentrations of 1–60 M and with a detection limit of 0.3 μM. Furthermore, using different concentrations of GSH, oxidized TMB can be reduced to TMB, and the color change from blue to nearly colorless can be observed by the naked eye (linear range, 1-60 μM; detection limit, 0.072 μM). The established colorimetric method can be successfully used to detect reduced GSH in tablets and injections with good selectivity and high sensitivity. The results of this study exhibited reliable consistency with the detection results obtained using high-performance liquid chromatography (HPLC). Therefore, the Fe-NDs colorimetric sensor designed in this study offers adequate accuracy and sensitivity.